2017
DOI: 10.1038/srep39985
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic comparison of Pik3ca and Pten signalling identifies the nucleotidase NT5C as a novel AKT substrate

Abstract: To identify novel effectors and processes regulated by PI3K pathway activation, we performed an unbiased phosphoproteomic screen comparing two common events of PI3K deregulation in cancer: oncogenic Pik3ca mutation (Pik3caH1047R) and deletion of Pten. Using mouse embryonic fibroblast (MEF) models that generate inducible, low-level pathway activation as observed in cancer, we quantified 7566 unique phosphopeptides from 3279 proteins. A number of proteins were found to be differentially-regulated by Pik3caH1047R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 65 publications
(83 reference statements)
2
16
0
Order By: Relevance
“…High-depth transcriptomics confirmed that heterozygosity for PIK3CA H1047R fails to induce widespread substantial transcriptional remodeling, whether chronically modelled in CRISPR-edited iPSCs or acutely induced in mouse embryonic fibroblasts (MEFs) by Cre expression, despite induction of canonical PI3K pathway activation in both cases (current study and Ref. ( 5, 28, 48 )). Similarly, iPSCs with heterozygous expression of PIK3CA E418K , a “non-hotspot” mutation, were transcriptionally indistinguishable from their isogenic wild-type controls.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…High-depth transcriptomics confirmed that heterozygosity for PIK3CA H1047R fails to induce widespread substantial transcriptional remodeling, whether chronically modelled in CRISPR-edited iPSCs or acutely induced in mouse embryonic fibroblasts (MEFs) by Cre expression, despite induction of canonical PI3K pathway activation in both cases (current study and Ref. ( 5, 28, 48 )). Similarly, iPSCs with heterozygous expression of PIK3CA E418K , a “non-hotspot” mutation, were transcriptionally indistinguishable from their isogenic wild-type controls.…”
Section: Discussionsupporting
confidence: 57%
“…1D ), with only 30 differentially-expressed genes (table S3 ). We also studied previously reported Pik3ca WT/H1047R mouse embryonic fibroblasts (MEFs) 48 h after Cre -mediated Pik3ca H1047R induction ( 28 ). Wild-type and Pik3ca WT/H1047R MEFs were superimposable on an MDS plot ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in prostate cancer cells with PTEN inactivation, AKT2 is exclusively required for cell-autonomous tumor maintenance (Chin et al, 2014), whereas in Pten +/− mice, the AKT1 isoform appears to suppresses prostate tumor development (Chen et al, 2006), while ablation of AKT2 has little impact (Xu et al, 2012). Global phospho-proteomic screening approaches have identified hundreds of novel phosphorylation sites that conform to the AKT consensus motif and have also provided new insights into potential AKT isoform-specific functions and substrates, many that await further validation (Lee et al, 2014; Moniz et al, 2017; Sanidas et al, 2014). Mechanisms that likely contribute to Akt isoform-specificity for downstream substrates include molecular features of individual isoforms, discrete subcellular localization, and relative expression levels in a given setting.…”
Section: Akt Isoform-specific Functions and Substratesmentioning
confidence: 99%
“…Thus, cytoskeletal remodeling driven by the PI3K-Rac axis drives not only cell motility but also metabolic reprogramming downstream of growth factor receptors. The role of PI3K signaling in effecting cytoskeletal remodeling is further highlighted by the recent identification of NT5C as a novel AKT substrate with a role in cytoskeletal remodeling that is mediated through interaction with ARP2/3 (Moniz et al, 2017). …”
Section: The Pi3k Pathway In Cellular and Organismal Metabolismmentioning
confidence: 99%